Hierarchical Polyaniline Spikes over Vegetable Oil derived Carbon Aerogel for Solid-State Symmetric/Asymmetric Supercapacitor. (20th June 2017) - Sahu, Vikrant; Marichi, Ram Bhagat; Singh, Gurmeet; Sharma, Raj Kishore
Graphical abstract: Abstract: Herein, we report an environment friendly methodology for the synthesis of carbon aerogel (CA) using bio-mass (mustard oil) as precursor. The synthesis process is highly reproducible and economical yet devoid of any sophisticated procedure and hazardous organic/inorganic chemicals. Exfoliated graphitic planes of carbon beads with enhanced inter-planer spacing are observed in synthesized CA with low bulk density (0.144 g cm −3 ) and high specific surface area (1032 m 2 g −1 ). The CA comprises of meso/microporosity with open pore microstructure. Symmetric supercapacitor cell (CA║CA) is fabricated to test the capacitive performance of CA in H2 SO4 -polyvinyl alcohol (H2 SO4 -PVA) gel as electrolyte. The CA║CA cell exhibits nearly symmetrical voltammograms up to working potential window of 2 V and impedance response demonstrates phase angle ∼80° indicating highly capacitive behavior. Polyaniline (PANI) spikes are further synthesized over CA using chemical oxidative polymerization route to introduce pseudocapacitive characteristics in addition to double layer capacitance. Solid-state symmetric (CA-PANI║CA-PANI) and asymmetric (CA║CA-PANI) supercapacitor cells are fabricated to examine the electrochemical performance. Fabricated CA║CA-PANI supercapacitor cell exhibits remarkable high power density (7.9 kW kg −1 ) and high energy density (55.6 Wh kg −1 ). The CA║CA-PANI cell is capable to power a light-emitting diode (LED) bulb effectively for 3.5 min by assembling two supercapacitors (1 × 1 cm 2 ).